Effects of Invasive Laser Acupuncture on Knee Osteoarthritis: Protocol for a Pilot Clinical Trial - Jae-Hong Kim; Changsop Yang; Jeong-Cheol Shin; Raeon Jang; Gwang-Cheon Park; Kyung-Min Shin; Byoung-Kab Kang; Ae-Ran Kim (MEDrang Inc., 2024)
Background: Invasive laser acupuncture (ILA) involves simultaneous application of focused laser irradiation and acupuncture. This study aims to explore the effects of ILA on knee osteoarthritis (KOA) through a pilot clinical trial. Methods: This prospective, patient-blinded, single-center, and parallel-arm pilot randomized controlled trial will enroll 45 patients with KOA randomized to the control, 830, and 650 groups. All patients will receive education on exercise and self-care. Their ILA treatment will correspond to their group (control group, sham; 830 group, 830 nm; 650 group, 650-nm wavelength laser) for 10 minutes once daily, twice weekly for 6 weeks at EX-LE4, ST35, ST34, SP10, SP9, GB34, and EXLE2 acupoints. Results: The primary endpoint will be changes in the visual analog scale (VAS) score of pain at rest and during activity 1 week after interventions (week 7). The secondary outcomes will be the responder rate; VAS, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) total, WOMAC pain subscale, WOMAC function subscale, European quality of life five-dimension five-level scale, and patient global assessment scores; and rescue medication doses. Safety outcome measures will include blood chemistry parameters, occurrence of adverse events, pulse rate, and blood pressure. The efficacy outcomes will be measured at baseline, visit after six treatments, 1 week after the last treatment, and 6 weeks after the last treatment. Conclusion: The findings will provide preliminary data on the effects of ILA on KOA.